Measurement and Normal Values, Pathologies, Interpretation of findings, and Interventional Ultrasound as part of student ultrasound education - Gschmack, Anna Maria; Karlas, Thomas; Lucius, Claudia; Barth, Gregor; Blaivas, Michael; Daum, Nils; Dong, Yi; Goudie, Adrian; Hoffmann, Beatrice; Jenssen, Christian; Kallenbach, Michael; Keil, Michael; Möller, Kathleen; Neubauer, Ricarda; Nourkami-Tutdibi, Nasenien; Recker, Florian; Ruppert, Johannes Peter; Sirli, Roxana; Weimer, Johannes; Westerway, Susan Campbell; Zervides, Constantinos; Dietrich, Christoph F. (Zeitschrift für Gastroenterologie, 2025)
Ultrasound diagnostics is a widely used, radiation-free, cost-effective, and bedside-applicable imaging technique. Given its numerous advantages and broad application, it appears reasonable to integrate practical use and theory into medical education at an early stage. Since the content of student ultrasound courses varies significantly on an international scale, the aim of this paper is to establish foundations for a more standardized approach to student’s ultrasound education (SUSE) especially with focus on abdominal ultrasound. This review examines to what extent measurements can be effectively incorporated into student ultrasound training and under which conditions the teaching of pathologies should be included in these courses. Additionally, the handling of false-positive and false-negative findings in student training is discussed. Considering the growing relevance of interventional ultrasound (INVUS), the paper further explores the extent to which interventional procedures should already be taught during SUSE.
Keywords: Ultrasound; Medical Student; Pathology; Measurement; Interventional Ultrasound